Le « géocyberespace » revisité - Henry Bakis (Netcom)
The geographical space change; with TIC innovations these changes are accelerating. Today new “spaces” are grafted on the human geographical space and are enabled by the telecommunications networks and new Information Technologies (Telecommunications, Data Processing, Audio-Visual technologies), such as ludic video spaces (video games…). Today new spaces are “grafted” on it and were made possible thanks to new technologies (telecommunications, data processing, audio-visual): they are ludic video spaces (video games…). Their recent outburst upheavals social, economic, legal and space related changes.